STRATEGY TO IMPROVE TEACHERS' PROFESSIONAL COMMITMENT THROUGH STRENGTHENING TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL CLIMATE, JOB SATISFACTION, AND TRUST IN PRIVATE VOCATIONAL SCHOOLS IN LEBAK DISTRICT, INDONESIA - Farid A.; Setyaningsih S.; Herfina; Hermawan A. (Russian Journal of Agricultural and Socio-Economic Sciences)
This study aims to find strategies and ways to improve teachers' professional commitment by conducting research related to the effect of transformational leadership, organizational climate, job satisfaction, and trust on teachers' professional commitment. The population in this study were teachers at private vocational schools in the Lebak district, totaling 716 teachers, using proportional random sampling techniques based on the Taro Yamane Formula, a selected sample of 257 teachers was obtained, spread according to their proportions in 45 private vocational schools in Lebak district. This study uses a survey method with a path analysis approach and is continued with SITOREM analysis. The results of the study indicate that there is a significant positive direct and indirect effect between transformational leadership, organizational climate, job satisfaction on teachers' professional commitment (Y) through trust The results of the SITOREM analysis show that based on the order of priority improvement, the indicators of the variables that need to be improved are: 1) Idealized effect, 2) Change Agent, 3) Response to superiors or leaders, 4) Response to the respect received, 5) Response to the work environment, 6) Response to career opportunities and self-development, 7) Organizational Values, 8) Virtuous leadership, 9) Applicable regulations, 10) Compensation and rewards, 11) Openness, 12) Work Regulation System, 13) Enthusiasm and involvement in work, 14) Dedication and desire for sustainability.